Price war in fast-food chains, Callao, 2025 - Chavez-Alvarez, Brescia Georgina; Mairena-Fox, Petronila Liliana (LACCEI, 2025)
The implementation of SDG 8 contributes to ensuring job creation and adequate working conditions for entrepreneurs. In particular, target 8.2 aims to increase productivity and, consequently, improve efficiency in fast-food businesses that require high added value due to their labour demand. The objective of the study was to analyse the relationship between price wars and the associated dimensions: prices above, equal to, and below those of the competition, in the district of Callao during the year 2025. The research adopted a quantitative, applied approach with a non-experimental design. A 20-item questionnaire was administered to a sample of 385 fast-food customers. 63% of respondents indicated that these businesses almost always or always set prices similar to those of their competitors in order to attract consumers. It was concluded that the highest percentage association was between the dimensions of prices above the competition and prices equal to the competition, reaching 41.47%.